Comparison of Phylogenetic Trees and Search for a Central Trend in the “Forest of Life” - Koonin, Eugene V. (Mary Ann Liebert, Inc., 2011)
The widespread exchange of genes among prokaryotes, known as horizontal gene transfer (HGT), is often considered to “uproot” the Tree of Life (TOL). Indeed, it is by now fully clear that genes in general possess different evolutionary histories. However, the possibility remains that the TOL concept can be reformulated and remain valid as a statistical central trend in the phylogenetic “Forest of Life” (FOL). This article describes a computational pipeline developed to chart the FOL by comparative analysis of thousands of phylogenetic trees. This analysis reveals a distinct, consistent phylogenetic signal that is particularly strong among the Nearly Universal Trees (NUTs), which correspond to genes represented in all or most of the analyzed organisms. Despite the substantial amount of apparent HGT seen even among the NUTs, these gene transfers appear to be distributed randomly and do not obscure the central tree-like trend.